Paradigm for the Application of the Dominus Litis Principle in the Indonesian State Administrative Court - Ahlul Fiqri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
In the case of efforts to establish a just rule of law state, judges need to actively find the material truth desired by the state administrative court and the Judicial Powers Act, including its practice in dispute resolution. Their activeness really helps people to get justice, namely following the duties of a judge. Among them are examining, deciding and resolving disputes, especially in examining State Administrative Decisions issued by State Institutions or Officials, which are contrary to applicable laws and regulations and general principles of good governance.